Mastectomized woman: experiencing sexuality - Ana Fátima Carvalho Fernandes; Raimunda Magalhães da Silva; Isabela Melo Bonfim; Jéssen Violene de Macêdo Santos (Rev Rene)
The study aimed at identifying aspects of sexuality in the process of readjustment of mastectomized women. We interviewed 19 women during the months of January and February of 2000, in a clinic belonging to the public network. The data were analyzed considering the relevance of the utterances contained in the categories ‘Meaning of sexuality’ and ‘Mastectomy and sexuality’. In the statements it was clear that the topic ‘sex’ was prohibited in the women’s family relationships: ‘... sex is something that I feel embarrassed to talk about until today, it makes sad because I enjoy it, but I don’t say that’. The participants of the study experienced moments permeated by various feelings, such as: shame, sadness, fear of not being accepted by the spouse, among others. Some women referred to the solitude and to the abandonment, stating that the situation of facing the disease and the mastectomy had been much more difficult: ‘For me it was very difficult to face that alone; if I had somebody...’ We concluded that the mastectomy is a source of traumas, questions and regrets, triggering changes in the woman’s life, as far as affection, society and family are concerned.